ghost (n); ghosts
ghost I mean, there must have been a lot of ghosts them times to be seen, an' especially back,way back,fifty years ago,sixty years ago. Yes (PRONUNCIATION ITEM) J.D.A. WIDDOWSON AUG 1973 Used I and Sup Not used